Public transport tracking through mobile application using radio frequency identification technology - Alam, Md. Rayhan; Haque, Enamul; Sajib, Shariar (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.